Responsible family ownership in small‐ and medium‐sized family enterprises: an exploratory study. (25th September 2014) - Aragón Amonarriz, Cristina; Iturrioz Landart, Cristina
Abstract : The concept of responsible ownership was originally developed with reference to large, publicly held firms. However, the relevance of small‐ and medium‐sized closely held firms, such as family firms, in all economies and the specific governance and organisational characteristics of these firms require further examination of the responsible ownership concept and its operationalisation. Based on the existing literature, we define the construct of responsible family ownership to fill this gap in responsible ownership theory. We propose a scale that can be used to assess the responsible family ownership construct in small‐ and medium‐sized family enterprises. The data used in this exploratory study were collected in an ad hoc survey answered by a representative sample of 84 small‐ and medium‐sized family enterprises. The study contributes to the responsible ownership literature by presenting the responsible family ownership construct, a key driver of balance in family and firm systems that is therefore critical to the health of small‐ and medium‐sized family enterprises. In addition, a scale is proposed as a means to operationalise the construct and to derive practical implications for the governance of this kind of firms.